2010
DOI: 10.1111/j.1468-3156.2008.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Down syndrome health screening – the Fife model

Abstract: Accessible summary• People with Down syndrome have their own health needs which may be different from those of the general population. • We wanted to know if we could pick up these health needs by inviting people to a regular clinic • We found that by coming to the clinic to have their health checked, some people found out about a health need that they might not have known about otherwise. SummaryPeople with Down syndrome have a greater risk of developing a range of health problems, including cardiac problems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Studies have also identified previously undiagnosed conditions that include serious and life threatening conditions including: heart disease (Walmsley, 2011;Wilson & Haire, 1990); hypertension (Baxter et al, 2006;McConkey, 2013;McConkey et al, 2002;Wilson & Haire, 1990); testicular cancer (Wilson & Haire, 1990); dementia (Baxter et al, 2006;Carlsen & Galluzzi, 1994;Cassidy et al, 2002;Jones et al, 2009); breast cancer (Baxter et al, 2006); diabetes (Baxter et al, 2006;Lennox et al, 2007;Walmsley, 2011); hypothyroidism (Barr et al, 1999;Baxter et al, 2006;Carlsen & Galluzzi, 1994;McConkey, 2013;Ryan & Sunada, 1997); mental health problems (Cassidy et al, 2002;Jones et al, 2009); cataracts (Lennox et al, 2001;McConkey et al, 2002;Ryan & Sunada, 1997); epilepsy (Lennox et al, 2007;Ryan & Sunada, 1997); arthritis ; compound fracture in leg and toxic levels of anticonvulsants (Gunsett et al, 1989); skin cancer (Carlsen & Galluzzi, 1994); and chronic pain, multiple sclerosis, colon cancer, pancreatic cancer, rectovaginal cancer and lung cancer (Ryan & Sunada, 1997).…”
Section: Outcomes Of Health Checksmentioning
confidence: 96%
See 4 more Smart Citations
“…Studies have also identified previously undiagnosed conditions that include serious and life threatening conditions including: heart disease (Walmsley, 2011;Wilson & Haire, 1990); hypertension (Baxter et al, 2006;McConkey, 2013;McConkey et al, 2002;Wilson & Haire, 1990); testicular cancer (Wilson & Haire, 1990); dementia (Baxter et al, 2006;Carlsen & Galluzzi, 1994;Cassidy et al, 2002;Jones et al, 2009); breast cancer (Baxter et al, 2006); diabetes (Baxter et al, 2006;Lennox et al, 2007;Walmsley, 2011); hypothyroidism (Barr et al, 1999;Baxter et al, 2006;Carlsen & Galluzzi, 1994;McConkey, 2013;Ryan & Sunada, 1997); mental health problems (Cassidy et al, 2002;Jones et al, 2009); cataracts (Lennox et al, 2001;McConkey et al, 2002;Ryan & Sunada, 1997); epilepsy (Lennox et al, 2007;Ryan & Sunada, 1997); arthritis ; compound fracture in leg and toxic levels of anticonvulsants (Gunsett et al, 1989); skin cancer (Carlsen & Galluzzi, 1994); and chronic pain, multiple sclerosis, colon cancer, pancreatic cancer, rectovaginal cancer and lung cancer (Ryan & Sunada, 1997).…”
Section: Outcomes Of Health Checksmentioning
confidence: 96%
“…The underlying rationale for the use of health checks is that: (1) primary care services tend to be reactive, responding to problems raised by patients (Martin, Roy, Wells, & Lewis, 1997); (2) people with intellectual disabilities may be unaware of the medical implications of symptoms they experience, have difficulty communicating their symptoms, or may be less likely to report them to medical staff (Beange, McElduff, & Baker, 1995;Kerr, McCulloch, & Oliver, 2003;Martin, Philip, Bates, & Warwick, 2004;McKenzie & Powell, 2004;Purcell, Morris, & McConkey, 1999); (3) carers may not always attribute the manifestations of clinical symptoms to physical or mental illness (Wilson & Haire, 1990); (4) as a result, health checks provide a way to detect, treat and prevent new health conditions in this population (Backer & Jervis, 2007;Barr, Gilgunn, Kane, & Moore, 1999;Cassidy, Martin, Martin, & Roy, 2002;Disability Rights Commission, 2006;Jones, Hathaway, Gilhooley, Leech, & MacLeod, 2009;Michael, 2008;Wilson & Haire, 1990). It has also been argued that health checks can help provide baseline information against which changes in health status can be monitored, a particular issue given the frequency of changes in paid carers supporting people with intellectual disabilities and the difficulties that people with intellectual disabilities may have in detecting and reporting longer term changes in health status (Martin, 2003;Jones et al, 2009).…”
Section: Rationale For Health Checksmentioning
confidence: 98%
See 3 more Smart Citations